Dimorphic Fungal Coinfection as a Cause of Chronic Diarrhea and Pancolitis - Eduar A. Bravo; Arturo J. Zegarra; Alejandro Piscoya; José L. Pinto; Raúl E. de los Rios; Ricardo A. Prochazka; Jorge L. Huerta-Mercado; Jaime Cok; Martin Tagle (Case Reports in Medicine)
Histoplasma capsulatum and Paracoccidioides brasiliensis are dimorphic fungi that cause systemic mycosis mostly in tropical South America and some areas of North America. Gastrointestinal involvement is not uncommon among these fungal diseases, but coinfection has not previously been reported. We report a patient with chronic diarrhea and pancolitis caused by paracoccidioidomycosis and histoplasmosis.